The house of Cross - Patterson, James, 1947- (Patterson, James, 1947- Alex Cross series., 2024)
"Supreme Court candidates are being murdered. Alex Cross and John Sampson are handed the case. In Washington, DC, the president-elect is planning her inauguration. The list of Supreme Court candidates is highly confidential-until it becomes evidence in Detective Alex Cross's toughest investigation. One candidate is gunned down. A second is stabbed. A third is murdered near midnight on a city street. Cross is the FBI's top expert in criminal behavior. For the sake of his family, his city, and his country, he must put himself in the most dangerous place there is: inside the mind of a diabolical killer"--